Strongly prime submodules and strongly 0-dimensional modules - Bilgin, Z.; Koç, S.; Özkirişci, N.A. (Algebra and Discrete Mathematics, 2019)
In this work, we study strongly prime submodules and strongly 0-dimensional modules. We give some equivalent conditions for being a strongly 0-dimensional module. Besides we show that the quasi-Zariski topology on the spectrum of a strongly 0-dimensional module satisfies all separation axioms and it is a metrizable space.